From field to plate: 50 years of plant-based food production and emerging risks to planetary and women’s health - Miele, Maria Julia; Pereira Coltri, Priscila; Ferreira Soares, Camila; Teixeira Souza, Renato; Carvalho Pacagnella, Rodolfo; Cecatti, José Guilherme; Teruel, Barbara (Frontiers in Nutrition, 2025)
IntroductionPlanetary health is a comprehensive approach that reveals the complex interconnections between sustainable human and environmental balance. This concept is rooted in the understanding that the health and progress of human civilization depend on thriving natural systems and their preservation. However, the profound impact of plant-based foods on both human and planetary health remains underestimated. Diet has the power to shape present health and compromise the future of entire generations.MethodsThis study analyzed 48 years (1974–2022) of trends in Brazilian agricultural production, focusing on plant-based foods and their potential risks to the environment and the health of women of reproductive age—a particularly vulnerable population. Using national databases, we explored associations between food production and consumption patterns within this demographic.ResultsAlthough rice and beans are traditionally central to Brazilian diets, production data suggest that the dominant crops available to women of reproductive age are soy and sugarcane. These crops are associated with numerous pesticide authorizations, suggesting high levels of contamination by toxic chemical residues.DiscussionOur findings suggest that plant-based diets represent a disruptive concept that requires careful revision, given the high contamination by toxic chemical residues in food, water, and humans. Beyond nutrient-based public policies, food management—from field to plate—must integrate food security to ensure a healthy and sustainable food system.